2013
DOI: 10.1186/1471-2377-13-18
|View full text |Cite
|
Sign up to set email alerts
|

Probable rapid eye movement sleep behavior disorder, nocturnal disturbances and quality of life in patients with Parkinson’s disease: a case-controlled study using the rapid eye movement sleep behavior disorder screening questionnaire

Abstract: BackgroundIncreasing evidence provides a clear association between rapid eye movement sleep behavior disorders (RBD) and Parkinson’s disease (PD), but the clinical features that determine the co-morbidity of RBD and PD are not yet fully understood.MethodsWe evaluated the characteristics of nocturnal disturbances and other motor and non-motor features related to RBD in patients with PD and the impact of RBD on their quality of life. Probable RBD (pRBD) was evaluated using the Japanese version of the RBD screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…yRBD experienced more depressive symptoms including loss of pleasure, crying, indecisiveness, and fatigue. A recent study by Suzuki et al[28] reported that PD patients who met the subjective criteria for RBD (using the Japanese version of the RBDSQ [23]) scored significantly higher on the BDI-II compared to a healthy control group but there were no differences between their RBD groups (including those with an RBDSQ≥5 but with no objective findings) on this measure. Nonetheless, in their study the RBD group reported significantly poorer emotional well-being on the subscale of the PDQ-39.…”
Section: Discussionmentioning
confidence: 99%
“…yRBD experienced more depressive symptoms including loss of pleasure, crying, indecisiveness, and fatigue. A recent study by Suzuki et al[28] reported that PD patients who met the subjective criteria for RBD (using the Japanese version of the RBDSQ [23]) scored significantly higher on the BDI-II compared to a healthy control group but there were no differences between their RBD groups (including those with an RBDSQ≥5 but with no objective findings) on this measure. Nonetheless, in their study the RBD group reported significantly poorer emotional well-being on the subscale of the PDQ-39.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, iRBD has been increasingly recognized as a precursor for other symptoms of neurodegenerative processes. Moreover, the frequency of RBD is reported to be up to 60% and some studies have shown a significant association between RBD and nighttime disturbances as well as quality of life in PD patients [4,5]. Given the potential risks that are associated with RBD and the available treatment options, it is recommended that screening for RBD should be performed as early as possible.…”
Section: Introductionmentioning
confidence: 98%
“…Some investigations [23,24] found that up to 75% of patients with REM sleep disorder developed a Parkinson-like disorder, or probable PD, which indirectly confirmed that very disturbed sleep quality may be a risk factor for the development of PD. In addition, the frequent coexistence of PD, RLS and PLM was observed in some patients, which is supported by the fact that we treat these disorders with the same or similar drugs [25].…”
Section: Discussionmentioning
confidence: 94%
“…In many studies [22,23], researchers found a correlation between REM SD and the consequent development of PD. Some investigations [23,24] found that up to 75% of patients with REM sleep disorder developed a Parkinson-like disorder, or probable PD, which indirectly confirmed that very disturbed sleep quality may be a risk factor for the development of PD.…”
Section: Discussionmentioning
confidence: 99%